Vacuum Cryo-Thermal Probe for Destruction of Malignant Tumors - Gasanov, Mikhail I.; Gurin, Alexandr V.; Klepikov, Valeriy V.; Larin, Marxen P.; Ponyatkovskiy, Stanislav A.; Prokhorov, Georgiy G. (Problems of Cryobiology and Cryomedicine, 2013)
The authors have designed, manufactured and tested several constructions of vacuum cryo-thermal probe intended for abalation of tumors by two- or three-fold freezing using liquid nitrogen and the following active heating up to 40°C. Needles of cryo-thermal probes are of 100 to 200 mm and from 1.5 to 2 mm outer diameter. The needle has two tubes coaxially arranged inside with the gaps in between, as well as the space for vacuum thermoisolation, channels for supply of liquid nitrogen into peripheral part of needle and retrace of nitrogen vapors. The end of needle is deprived of vacuum thermoisolation over a length of 20 mm and may be cooled by liquid nitrogen or heated by warmed nitrogen vapors, herewith the temperature of the remaining outer part of needle differs insignificantly from the room temperature. Cryostat of 10 l is used to supply liquid and nitrogen vapors into cryo-thermal probe. Due to the fact that cryostat may be placed in 0.5-1 m from a patient the hydraulic resistance of pipeline connecting the cryostat with cryo-thermal probe is significantly decreased, and for effective cooling of probe it is sufficient to maintain the pressure of 2-4 Bar in cryostat. Probl Cryobiol Cryomed 2013; 23(2):152-161.